Soil resistance to penetration in tillage systems and tractor speed - Nagahama, Hideo de Jesus; Cortez, Jorge Wilson; Pimenta, Wisy Alves; Patrocinio Filho, Antonio Pereira; Souza, Elder Barboza de (Comunicata Scientiae, 2016)
The continuous use of tillage equipment without variation of the work depth can lead to soil compression problems. This study aimed to evaluate the spatial variability of soil resistance to penetration (RP) in a yellow ultisol profile in different tillage systems and tractor-equipment speeds. The experiment was carried out at the Agricultural Sciences Campus – UNIVASF, Petrolina- PE, Brazil, in randomized blocks with split plot with four repetitions. The treatments consisted of five tillage systems applied to the plots: without the first soil preparation, tandem grid and moldboard plow, 0.56 m off-set grid discs, 0.61 m off-set grid disc plus tandem grid and chisel plow. For the subplots, the speeds of the tractor-equipment used were: 2.45 km h‑1 (L1), 3.88 km h-1 (L2), 5.72 km h-1 (L3) and 6.50 km h-1 (H1). For the soil data collection and the RP determination, an electronic penetrometer was used, determining the sample profile moisture. Data analysis was carried out based on geostatistics and isoline maps. It can be verified the operationarea of the active organs of the equipment, the zoning of compacted areas (RP) and the RP levels of the studied profile. The lower RP was obtained when the tandem grid plus the chisel plow was used.